Anti-inflammatory and biologic drugs for atopic dermatitis: a therapeutic approach in children and adolescents - Caffarelli, Carlo; Giannetti, Arianna; Giannì, Giuliana; Ricci, Giampaolo (Frontiers in Medicine, 2023)
Atopic dermatitis (AD) is a chronic inflammatory disease with a heterogeneous pathogenesis correlated with dysregulation of the immune system and a prevalence of the T2-mediated immune pathway. Recent understanding of the pathogenesis of AD has allowed the development of new drugs targeting different mechanisms and cytokines that have changed the treatment approach. The aim of this review is to update knowledge on the standard of care and recent advancements in the control of skin inflammation. In light of recent guidelines, we report on the clinical efficacy of novel treatments, with special attention to situations where biologics and small molecules are involved.